SIKAP PEROKOK AKTIF DALAM MENANGGAPI PERINGATAN BAHAYA MEROKOK PADA IKLAN ROKOK DI TELEVISI (Studi Masyarakat Desa Talang Jambu Kecamatan Kerkap Kabupaten Bengkulu Utara) - Meta Juwita Sari; Yanto Yanto; Sapta Sari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
The attitude of active smokers in smoking bans on cigarette advertisements can communicate their products as commodities that are connected with glamor, energy and lifestyle. The cigarette industry leads children to become beginner smokers through advertisements, promotions that are present in television media. Cigarette companies compete to make advertisements as creative as possible with the aim of increasing sales. Based on the background above the formulation of the research problem is how the attitudes of active smokers in responding to the warning of hazards on cigarette advertisements on television. Based on the research problem above, the aim of the study is to find out the attitudes of active smokers in responding to the warning of hazards on cigarette advertisements on television. The methodology in this study uses qualitative research with data collection technique of observation, interviews and documentation.The results of the study stated that the informants were afraid with the contents of message on public service advertisements (ILM) about the dangers of smoking. This can be seen from the interview quote from the informant's answer. The informant saw ILM about the dangers of smoking being broadcast on television. In this study, almost all of the informants said that first the informants began to try to smoke because there was a feeling of insecurity if they did not smoke while gathering with friends in the neighborhood. There were also informants who smoked because of great curiosity, so the intention was to try to smoke cigarettes. Even the informant who said that one of the factors that made the informant curious and wanted to try cigarettes was because the informant saw the parents of informants who smoked at home. Active smokers try to smoke because there are influences from family factors and the environment where they live. Based on this this research, it is expected that the environment can help active smokers no longer depend on cigarettes.